Suscetibilidade de populações do percevejo-marrom Euschistus heros (Fabricius, 1798) e do percevejo barriga-verde Dichelops furcatus (Fabricius, 1775) a inseticidas - Somavilla, Junior Cesar (2020)
The neotropical brown stink bug, Euschistus heros (Fabricius, 1798), and the green belly stink bug, Dichelops furcatus (Fabricius, 1775), are important sucking pests that attack cultivated plants in Brazil. The control of these species is usually carried out with the use of chemical insecticides, which belong to a few chemical groups (pyrethroids, neonicotinoids and organophosphates). Based on this, we conducted bioassays to evaluate the susceptibility of E. heros and D. furcatus to insecticides. In the first study, populations of E. heros and D. furcatus were collected from 2017 to 2019 in soybean and wheat fields, and exposed to distinct concentrations of the acephate, thiamethoxam, bifenthrin and lambda-cyhalothrin in dip-test bioassays using fresh green bean pods (Phaseolus vulgaris). Field populations of E. heros exhibited low variation in the susceptibility to acephate (LC50 = 172.2 to 1,008 µg a.i./ml) and thiamethoxam (LC50 = 28.8 to 433.9 µg a.i./ml), resistance ratios less than 5.9 and 15.1-fold, respectively. In contrast, these populations had higher variation in the susceptibility to bifenthrin (LC50 = 26.7 to 636.1 µg a.i./ml) and lambda-cyhalothrin (LC50 = 10.0 to 636.1 µg a.i./ml); resistance ratios reaching 23.8 and 63.6-fold, respectively. Susceptibility monitoring data indicated a higher susceptibility of E. heros to the manufacturers field‐recommended rates of acephate, lambda-cyhalothrin + thiamethoxam and bifenthrin + acetamiprid than lambda- cyhalothrin. Populations of D. furcatus exhibited low variation in the susceptibility to acephate (LC50 = 219.2 to 614.1 µg a.i./ml), bifenthrin (LC50 = 62.8 to 197.4 µg a.i./ml), and lambda- cyhalothrin (LC50 = 189.5 to 2,538 µg a.i./m1). Resistance ratios for these insecticides were less than 13.4-fold. In the second study, the technical grade insecticides: acefate, thiamethoxam, bifenthrin and lambda-cyhalothrin were diluted in acetone PA, and applied topically at the dorsum of each insect (2 µl/stink bug). In this study, populations of E. heros presented low variation in the susceptibility to acephate (LD50 = 0.22 to 0.69 µg a.i./stink bug), bifenthrin (LD50 = 0.021 to 0.10 µg a.i./stink bug) and thiamethoxam (LD50 = 0.0046 to 0.032 µg a.i./stink bug); resistance ratios less than 8.2-fold. In contrast, a higher variation in susceptibility to lambda-cyhalothrin was found (LD50 = 0.073 to 0.35 µg a.i./stink bug); resistance ratios less than 15.7-fold. The diagnostic doses of 1.30; 0.34; 0.36 and 1.73 µg a.i./stink bug were defined for monitoring the susceptibility of E. heros to acephate, thiamethoxam, bifenthrin and lambda- cyhalothrin, respectively. Field populations of D. furcatus had low variation in the susceptibility to acephate (LD50 = 0.30 to 0.53 µg a.i./stink bug), thiamethoxam (LD50 = 0.066 to 0.14 µg a.i./stink bug), and lambda-cyhalothrin (LD50 = 0.27 to 0.56 µg a.i./stink bug), with resistance ratios less than 2.1-fold. The results indicate a lower susceptibility of E. heros populations to bifenthrin and lambda-cyhalothrin. Populations of D. furcatus had similar susceptibility to acephate, thiamethoxam, bifenthrin and lambda-cyhalothrin.